THE TWISTS AND TURNS OF CHARACTERS IN THE NOVEL "BALANCE" BY ULUGBEK HAMDAM - Kuchimova, Gulmera (Журнал иностранных языков и лингвистики, 2022)
Usually, when a person starts reading a new novel and finishes it, the feelings and impressions are not the same. You will be relieved when the work you started reading with interest is finished. The events of the play will once again come alive before your eyes like film tapes, and you will get some kind of satisfaction and interest. But it doesn’t seem that way if you don’t analyze Ulugbek Hamdam’s work "Equilibrium" in depth. The novel seems to start the same way and end the same way.